The development of an Interdepartmental Relationship Framework, Soft Internal Marketing Architecture (SIMA) and Strategy Development Tool - Marzec, Peter Edward (2008)
The issue of poor communication and integration are frequent problems within businesses, especially the more mature they are. This project considers this issue and begins the work in establishing clearly defined roles of the business department and introduces an interdepartmental relationships framework to aid in the understanding of the business by addressing the question of how can we establish how the business areas fit together? The current research is predominately academically based, however the overall project is very much focused on practical application so this paper is suggested as an introductory and foundation phase of a larger project, with subsequent stages envisaged to include a practical implementation framework and empirical case studies. This paper subsequently constructs the necessary details for a robust linkage framework and details the application of 2 possible outputs of such a framework, a "Soft" Internal Marketing framework and a Strategy Development model, and suggests 3 additional outputs that could be developed in future research. This research may appeal to academics on several fronts as detailed in the conclusion, for example by summarising the literature on the interdepartmental relationships, proposing a new methodology to justify departmental linkages and by developing an implementation framework for internal marketing and an associated "intraprise" evaluation dashboard.